Lifelong learning challenges: Proactive, reactive or inactive? - Krishnasamy, Hariharan N.; Said, Shahrul Niza (2010)
Lifelong learning transcends age and the narrow confines of the classroom. The advances in technology, globalization, economic advancement and a range of other factors have contributed to the need for lifelong learning. In line with the global trend to provide viable alternatives to conventional educational systems, the Malaysian government has provided impetus for lifelong learning through its Third Outline Perspective Plan, the 8th Malaysia Plan and the 9th Malaysia Plan. The opportunity to pursue off-campus learning programs paves the way for lifelong learning. The present study focuses on an off-campus program offered by a tertiary-level institution in Malaysia, that is, Universiti Utara Malaysia. 20 students enrolled in UUM’s off-campus undergraduate program were interviewed in 2009 and 2010. Participants had completed their first or second semester of study. Interviews regarding students’ readiness for self-directed learning indicated that several issues needed to be addressed if more students were expected to successfully complete their programs. While some students coped well with independent learning, a sizeable number of students needed more guidance on strategies that could help with independent learning. Issues that need to be addressed by the university include access to resources, academic guidance, effective study techniques, and meeting deadlines.